Rapid Investigation of Functional Roles of Genes in Regulation of Leaf Senescence Using Arabidopsis Protoplasts - Doan, Phan Phuong Thao; Kim, Jin Hee; Kim, Jeongsik (Frontiers in Plant Science, 2022)
Leaf senescence is the final stage of leaf development preceding death, which involves a significant cellular metabolic transition from anabolism to catabolism. Several processes during leaf senescence require coordinated regulation by senescence regulatory genes. In this study, we developed a rapid and systematic cellular approach to dissect the functional roles of genes in senescence regulation through their transient expression in Arabidopsis protoplasts. We established and validated this system by monitoring the expression of a luciferase-based reporter that was activated by SEN4 and SAG12 promoters, early and late senescence-responsive genes, and effectors of identified positive and negative senescence regulators. Overexpression of positive senescence regulators, including ORE1, RPK1, and RAV1 increased the expression of both SEN4- and SAG12-LUC while ORE7, a negative senescence regulator decreased their expression. Consistently with overexpression, knockdown of target genes using amiRNAs resulted in opposite SAG12-LUC expression patterns. The timing and patterns of reporter responses induced by senescence regulators provided molecular evidence for their distinct kinetic involvement in leaf senescence regulation. Remarkably, ORE1 and RPK1 are involved in cell death responses, with more prominent and earlier involvement of ORE1 than RPK1. Consistent with the results in protoplasts, further time-series of reactive oxygen species (ROS) and cell death assays using different tobacco transient systems reveal that ORE1 causes acute cell death and RPK1 mediates superoxide-dependent intermediate cell death signaling during leaf senescence. Overall, our results indicated that the luciferase-based reporter system in protoplasts is a reliable experimental system that can be effectively used to examine the regulatory roles of Arabidopsis senescence-associated genes.